2023
DOI: 10.1182/bloodadvances.2023011050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preexisting autoimmune disease on myelodysplastic syndromes outcomes: a population analysis

Diego Adrianzen-Herrera,
Andrew D. Sparks,
Rohit Singh
et al.

Abstract: Preexisting autoimmune disease affects 10-30% of patients with myelodysplastic syndromes (MDS). Studies comparing outcomes in MDS patients with and without autoimmune disease show discordant results. Using Surveillance, Epidemiology, and End Results (SEER)-Medicare, we conducted a population analysis to define the impact of autoimmunity on MDS outcomes. Cases were ascertained between 2007 - 2017 and claim algorithms employed to identify autoimmune disease, demographic characteristics, comorbidity scores, MDS h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…For instance, a retrospective study of 1408 MDS patients reported that patients with MDS with ADs achieved significantly better OS than those without ADs after adjusting for covariates such as age and R-IPSS (Revised International Prognostic Scoring System) classification [20]. This finding compares favorably with another retrospective study of 15,227 patients, which reported that the risk of death decreased by 11% in MDS patients with ADs after controlling for covariates such as age, sex, rural residence, immunosuppressive therapy, higher MDS histologic risk, and transfusion dependence [17]. Although the exact reason for this positive association between ADs and survival remains unknown, it might be attributed to the fact that ADs have a neutral or protective role in the later stages of MDS when genetic mutations and clonal evolution are the underlying drivers of the disease.…”
Section: Impact Of Ads On the Survival Of Mds Patientssupporting
confidence: 48%
See 1 more Smart Citation
“…For instance, a retrospective study of 1408 MDS patients reported that patients with MDS with ADs achieved significantly better OS than those without ADs after adjusting for covariates such as age and R-IPSS (Revised International Prognostic Scoring System) classification [20]. This finding compares favorably with another retrospective study of 15,227 patients, which reported that the risk of death decreased by 11% in MDS patients with ADs after controlling for covariates such as age, sex, rural residence, immunosuppressive therapy, higher MDS histologic risk, and transfusion dependence [17]. Although the exact reason for this positive association between ADs and survival remains unknown, it might be attributed to the fact that ADs have a neutral or protective role in the later stages of MDS when genetic mutations and clonal evolution are the underlying drivers of the disease.…”
Section: Impact Of Ads On the Survival Of Mds Patientssupporting
confidence: 48%
“…Two of these studies showed that MDS patients with ADs had inferior OS compared to those without ADs [18,21]. In contrast, the other two studies reported that ADs were associated with a considerable decrease in mortality risk [17,20]. Moreover, another study reported that OS was better when ADs were diagnosed simultaneously with MDS or after the MDS diagnosis (HR: 0.1; p = 0.008 and HR: 0.024; p = 0.009) [19].…”
Section: Clinical Outcomes Of Mds Based On the Presence Of Adsmentioning
confidence: 99%
“…A Spanish study found shorter survival in this subset of patients with MDS combined with autoimmune disease, especially in low-risk MDS patients [10] . This can be explained by the fact that patients with MDS combined with autoimmune diseases have more severe immune dysregulation, which leads to more severe bone marrow failure and disease progression [28] .Conversely, it has been shown that MDS patients combined with autoimmune disease appears to have a better survival bene t. Recently,a US study retrospectively analyzed 15,277 patients with MDS from the SEER Medicare database, of whom 2,442 (16%) had pre-existing autoimmune disease, which reduced the risk of death by 11%.In low-risk MDS, the presence of pre-existing autoimmune disease was associated with an increased risk of leukemic transformation [29] . Another case-control study showed that this group of patients with MDS combined with autoimmune disease had better OS and lower leukemic transformation rates [4] .…”
Section: Discussionmentioning
confidence: 99%